2014
DOI: 10.7178/jeit.15
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarginine Dimethylaminohydose(DDAH) Overexpression Attenuates Agricultural Organic Dust Extract-Induced Inflammation

Abstract: Modern, industrialized farming practices have lead to working conditions that include high levels of airborne dust. Agricultural workers inhale these complex organic dusts on a daily basis, leading to airway inflammation and higher risk for developing chronic obstructive pulmonary disease. The mechanisms regulating the organic dust-induced airway inflammatory response are not well-defined. We investigated whether overexpression of dimethylarginine dimethylaminohydrolase (DDAH) would lead to diminished pulmonar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In humans, OD exposure is associated with increases in oxidative stress markers (28, 44). Bailey et al (3) demonstrated that overexpression of dimethylarginine dimethylaminohydrolase, which inactivates the nitric oxide inhibitor asymmetric dimethylarginine by hydrolyzing it into citrulline and dimethylamine inhibitor, was effective in attenuating neutrophilia induced by OD exposure in mice. Taken together, our data and human study data suggest that exposure to OD exposure induces upregulation of antioxidant pathways, specifically NRF-2, and these changes are associated with neutrophil presence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, OD exposure is associated with increases in oxidative stress markers (28, 44). Bailey et al (3) demonstrated that overexpression of dimethylarginine dimethylaminohydrolase, which inactivates the nitric oxide inhibitor asymmetric dimethylarginine by hydrolyzing it into citrulline and dimethylamine inhibitor, was effective in attenuating neutrophilia induced by OD exposure in mice. Taken together, our data and human study data suggest that exposure to OD exposure induces upregulation of antioxidant pathways, specifically NRF-2, and these changes are associated with neutrophil presence.…”
Section: Discussionmentioning
confidence: 99%
“…Because severe pulmonary neutrophilia is a hallmark of OD exposure in both human and animal models, mostly as assessed by BAL fluid analyses (3,10,20), we sought to address the importance of neutrophils using a granulocyte depletion antibody, anti-Ly6G. Despite not reaching 100% reduction in neutrophils, the anti-Ly6G effect on cell depletion was selective for neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Aggravated capillary damage, inflammation, and oxidative stress following successful reperfusion are possible explanations for the case. Putative mechanisms for these phenomena are interaction of reperfusion-induced hyperfiltration, high intraglomerular capillary pressure, oxidative stress, increased polymorphonuclear cell infiltration, and inflammation [ 13 , 14 ]. In the early stage post renal transplantation, the glomerular filtration membrane is constantly exposed to high pressure for several days, which may lead to proteinuria and potential tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…Organic dust that had settled onto horizontal surfaces in a moderately-sized (approximately 500–700 head) swine confinement facility was collected as previously described (K. Bailey et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…This inhibition of the NO pathway can be reversed with dimethylarginine dimethylaminohydrolase (DDAH), an inhibitor of ADMA (Tran, Leiper, Vallance 2003). Thus, transgenic mice that overexpress DDAH demonstrate a decreased in vivo inflammatory response to hog barn dust (K. Bailey et al 2014).…”
Section: Introductionmentioning
confidence: 99%